International review of social history, vol. 57, part 2 - august 2012
- Marcel van der Linden, David Montgomery (19272011) - Chitra Joshi, 'Dak Roads, Dak Runners, and the Reordering of Communication Networks' - E. Attila Aytekin, 'Peasant Protest in the Late Ottoman Empire: Moral Economy, Revolt, and the Tanzimat Reforms' - Frank Wolff, 'Eastern Europe Abroad: Exploring Actor-Networks in Transnational Movements and Migration History, The Case of the Bund' Review Essay - Rosemarijn Hoefte, 'Plantations and Labour in the Caribbean in the Long Nineteenth Century' - Tine De Moor, 'What Do We Have in Common? A Comparative Framework for Old and New Literature on the Commons' Book reviews